2022
DOI: 10.3390/jcm11226808
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Enucleation of Prostate Could Increase Testosterone Levels in Hypotestosteronemic Patients with Bladder Outlet Obstruction

Abstract: Background: We evaluated the impact of endoscopic enucleation of the prostate on testosterone levels in hypotestosteronemic patients with bladder outlet obstruction. Methods: We enrolled 294 men with lower urinary tract symptoms (LUTS) who received surgery between January 2019 and December 2020 in simple tertiary centre. The inclusion criteria were as follows: being a male patient aged 45–95 years and having recurrent urinary tract infection, having previously failed medical treatment for LUTS or urine retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…6 Furthermore, our investigations have shown that patients with low testosterone levels who underwent anatomical endoscopic enucleation of the prostate saw a postoperative increase in testosterone, suggesting that effective LUTS treatment could also confer an endogenous TRT effect. 7 Given the multifaceted nature of LUTS and their significant impact on patients' quality of life, our discussion underscores the importance of considering a broader spectrum of factors, including nocturia, NP, and testosterone levels. These factors serve as indicators for monitoring the extent to which LUTS may be disrupting the circadian rhythm.…”
Section: Dear Editormentioning
confidence: 98%
“…6 Furthermore, our investigations have shown that patients with low testosterone levels who underwent anatomical endoscopic enucleation of the prostate saw a postoperative increase in testosterone, suggesting that effective LUTS treatment could also confer an endogenous TRT effect. 7 Given the multifaceted nature of LUTS and their significant impact on patients' quality of life, our discussion underscores the importance of considering a broader spectrum of factors, including nocturia, NP, and testosterone levels. These factors serve as indicators for monitoring the extent to which LUTS may be disrupting the circadian rhythm.…”
Section: Dear Editormentioning
confidence: 98%